KAJIAN RESPON CALON PENUMPANG ANGKUTAN MASSAL DI KOTA BANDA ACEH - Mufazzil Yusra; Renni Anggraini; Muhammad Isya (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract : Mass Public Transportation System could be an alternative policy in solving the problem of congestion in the city of Banda Aceh. Given the problems such as congestion and uncontrolled number of private transport is supported by the lack of a secondary network that serves as a divider traffic flow or collector (collector) the movement of vehicles began to appear. The government the city of Banda Aceh has provide Bus Rapid Transit (BRT) with the name